Energy Near-Degeneracy Driven Covalency Analyzed by a Two-Electron Two-Orbital Model (Communications in Computational Chemistry, 2025)
A simple model based on the two-electron two-orbital textbook problem is presented and used to analyze pairwiseinteratomic interactions in metal-ligand bonding. In particular the two types of covalency discussed during the last decade foractinide-ligand interactions, overlap/interaction driven and energy-near-degeneracy driven covalency, as well as their influenceon the bond strengths and interatomic charge build-up are discussed. The hydration complexes ${\rm M}({\rm H}_2{\rm O})^{4+}_n$ of selected tetravalentlanthanide and actinide ions are used to probe the performance of the model for an analysis of calculations as well as forpredictions.